Missed detections of influenza A(H1)pdm09 by real-time RT–PCR assay due to haemagglutinin sequence mutation, December 2017 to March 2018, northern Viet Nam (Western Pacific Surveillance and Response, 2019)
Introduction: There are two methods of reverse transcription polymerase chain reaction (RT–PCR) that have been the common methods to detect influenza infections: conventional and real-time RT–PCR. From December 2017 to March 2018, several missed diagnoses of influenza A(H1)pdm09 using real-time RT–PCR were reported in northern Viet Nam. This study investigated how these missed detections occurred to determine their effect on the surveillance of influenza.Methods: The haemagglutinin (HA) segments of A(H1N1)pdm09 from both real-time RT–PCR positive and negative samples were isolated and sequenced. The primer and probe sets in the HA gene were checked for mismatches, and phylogenetic analyses were performed to determine the molecular epidemiology of these viruses.Results: There were 86 positive influenza A samples; 32 were A(H1)pdm09 positive by conventional RT–PCR but were negative by real-time RT–PCR. Sequencing was conducted on 23 influenza (H1N1)pdm09 isolates that were recovered from positive samples. Eight of these were negative for A(H1)pdm09 by real-time RT–PCR. There were two different mismatches in the probe target sites of the HA gene sequences of all isolates (n = 23) with additional mismatches only at position 7 (template binding site) identified for all eight negative real-time RT–PCR isolates. The prime target sites had no mismatches. Phylogenetic analysis of the HA gene showed that both the positive and negative real-time RT–PCR isolates were grouped in clade 6B.1; however, the real-time RT–PCR negative viruses were located in a subgroup that referred to substitution I295V.Conclusion: Constant monitoring of genetic changes in the circulating influenza A(H1N1)pdm09 viruses is important for maintaining the sensitivity of molecular detection assays.